32.4k views
5 votes
2/5(1/3x-15/8)-1/3(1/2-2/3x)

User Insomniac
by
6.0k points

1 Answer

6 votes

Answer:


(16)/(45)x-(11)/(12)

Explanation:

We are given that an expression


(2)/(5)(1/3x-15/8)-(1)/(3)(1/2-2/3x)

We have to find the equivalent expression.


(2)/(5)((1)/(3)x-(15)/(8))-(1)/(3)((1)/(2)-(2)/(3)x)


(2)/(5)* (1)/(3)x-(2)/(5)* (15)/(8)-(1)/(3)* (1)/(2)-(1)/(3)* (-(2)/(3)x)

Using the the property


a\cdot (c-b)=a\cdot c-a\cdot b


(2)/(5)(1/3x-15/8)-(1)/(3)(1/2-2/3x)


=(2)/(15)x-(3)/(4)-(1)/(6)+(2)/(9)x


=(6x+10x)/(45)+(-9-2)/(12)


=(16)/(45)x-(11)/(12)


(2)/(5)(1/3x-15/8)-(1)/(3)(1/2-2/3x)=(16)/(45)x-(11)/(12)

User Benjaminmgross
by
5.4k points